Long‐term declines of native trees in an oceanic island's tropical forests invaded by alien plants. Issue 1 (20th October 2016) - Florens, F.B. Vincent; Baider, Cláudia; Seegoolam, Nooshruth B.; Zmanay, Zeyn; Strasberg, Dominique
Abstract: Question: How did the native and alien woody plant communities of protected lowland wet forests of a tropical oceanic island change in the presence of understorey invasive alien plants over the medium (21–27 yrs) and longer term (68 yrs)? Location: Bel Ombre, Brise Fer and Macchabé forests in the Black River Gorges National Park (BRGNP), Mauritius (20°22′10″– 20°28′17″ S, 57°24′45″– 57°27′12″ E). Methods: Random and replicated vegetation plots were sampled in two protected forest areas whose communities of woody plants were surveyed 21 and 27 yrs previously, and in another protected and similar forest that was surveyed 68 yrs earlier, to identify species and measure stem diameters so as to permit comparisons at the three sites over these time periods. Results: Invasion by woody alien plants has progressed through time at all three sites, comprised mostly of the understorey and shade‐tolerant Strawberry guava ( Psidium cattleianum ). Concomitantly, although reductions in native woody plant species richness of large trees (≥10 cm DBH) were not statistically significant at the community level, their densities and basal area had roughly halved in 68 yrs. Comparisons with the studies 21–27 yrs previously confirmed the tendency towards a reduction in density of larger trees, besides indicating a trend towards decline in species richness of smaller understorey trees. Conclusion: An unabated replacement of native by alien trees over the longer term is occurring in protected areas of the lowland wet forests of the BRGNP and presumably in other similarly invaded areas. Our work stresses the importance of long‐term monitoring in elucidating impacts of invasive alien plants at the community level, particularly when dealing with slow‐growing and long‐lived species. Plausible mechanisms bringing about the observed changes and that have been found at the same or similar sites, include reduced regeneration, growth, production of flowers and fruits and increased mortality of native trees when these grow among invasive alien plants. The control of invasive alien plants, where they invade tropical forests, should be a central conservation objective even in better preserved and well protected areas. Abstract : Early surveys of closed canopy forests in protected areas in Mauritius enabled unraveling long‐term impacts of alien plants on native tree communities, showing a progressing understory invasion while large native trees halved in density over 68 yrs. Much of Mauritius' protected areas now offer a desolated view of dead and dying trees like here in Black River Gorges National Park.